Selective cutoff reporting in studies of the accuracy of the Patient Health Questionnaire‐9 and Edinburgh Postnatal Depression Scale: Comparison of results based on published cutoffs versus all cutoffs using individual participant data meta‐analysis - Dipika Neupane; Brooke Levis; Parash M. Bhandari; Brett D. Thombs; Andrea Benedetti; DEPRESsion Screening Data (DEPRESSD) Collaboration (International Journal of Methods in Psychiatric Research, 2021)
Abstract Objectives Selectively reported results from only well‐performing cutoffs in diagnostic accuracy studies may bias estimates in meta‐analyses. We investigated cutoff reporting patterns for the Patient Health Questionnaire‐9 (PHQ‐9; standard cutoff 10) and Edinburgh Postnatal Depression Scale (EPDS; no standard cutoff, commonly used 10–13) and compared accuracy estimates based on published cutoffs versus all cutoffs. Methods We conducted bivariate random effects meta‐analyses using individual participant data to compare accuracy from published versus all cutoffs. Results For the PHQ‐9 (30 studies, N = 11,773), published results underestimated sensitivity for cutoffs below 10 (median difference: −0.06) and overestimated for cutoffs above 10 (median difference: 0.07). EPDS (19 studies, N = 3637) sensitivity estimates from published results were similar for cutoffs below 10 (median difference: 0.00) but higher for cutoffs above 13 (median difference: 0.14). Specificity estimates from published and all cutoffs were similar for both tools. The mean cutoff of all reported cutoffs in PHQ‐9 studies with optimal cutoff below 10 was 8.8 compared to 11.8 for those with optimal cutoffs above 10. Mean for EPDS studies with optimal cutoffs below 10 was 9.9 compared to 11.8 for those with optimal cutoffs greater than 10. Conclusion Selective cutoff reporting was more pronounced for the PHQ‐9 than EPDS.